2022
DOI: 10.48550/arxiv.2206.05461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kolmogorov's Theorem for Degenerate Hamiltonian Systems with Continuous Parameters

Abstract: In this paper, we study Kolmogorov type theorems for small perturbations of certain degenerate Hamiltonian systems, indexed by a parameter ξ, with H(y, x, ξ) = ω(ξ), y + εP(y, x, ξ, ε), where ε > 0. We assume the frequency map ω is continuous about ξ, and the perturbation function P(y, x, •, ε) is Hölder continuous about ξ. We prove that persistent invariant tori possess the same frequency as the unperturbed tori, under certain topological degree condition and weak convexity condition for the frequency mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…See (A0) in section 1.3 for details. It should be pointed out that the topological degree can also be used to study frequency-preserving in the KAM theory, see [5,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…See (A0) in section 1.3 for details. It should be pointed out that the topological degree can also be used to study frequency-preserving in the KAM theory, see [5,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Considering Diophantine nonresonance, the invariant tori are shown in classical KAM theorems to be preserved under analytic settings. It should be pointed out that, if a constant Diophantine frequency is prescribed in advance, one could obtain KAM persistence with frequency being unchanged by proposing certain nondegeneracy or transversality conditions, which preserves more dynamics from the perturbed one, see Salamon [35], Du et al [11] and Tong et al [38] for instance, respectively, and this analytic torus is interestingly shown to be never isolated by Eliasson et al in [13]. Therefore, beyond analyticity, it is still interesting to touch the minimum initial regularity for Hamiltonian to which KAM could applied.…”
Section: Introductionmentioning
confidence: 99%